Purified by fire : a history of cremation in America - Prothero, Stephen R. (University of California Press, 2001)
'Purified by Fire' tells the story of cremation's rise from notoriety to legitimacy and takes a provocative new look at important transformations in the American cultural landscape over the last 150 years.